Education about Early Asking and Bounding Initiations Attachment Against the Mother's Readiness - Delima, Mera; Andriani, Yessi; Putri, Rahmatul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the effect of education about early breastfeeding initiation and bounding attachment on maternal readiness for the breastfeeding process at BPS Bunda Bukittinggi. This type of research uses the Pre-experiment method with the design of one group pretest and posttest. In this study with the mean value of the readiness of mothers to breastfeed before doing education was 57,33 which then increased to 63,80 and the value of p Value 0,000 (p <0.05), meaning that there is an effect of education about the initiation of early breastfeeding and bounding attachment to maternal readiness for the breastfeeding process in the BPS Bunda Bukittinggi in 2019. It was concluded that education about early breastfeeding initiation and bounding attachment can increase knowledge in readiness for breastfeeding in pregnant women. Keywords: Bounding Attachment Early, Breastfeeding Initiation, Maternal Readiness For Breastfeeding